Gameplay and physical activity behaviors in adult video game players - Haylei Scoggins; Ryan R. Porter; Robyn Braun-Trocchio (Frontiers in Sports and Active Living)
IntroductionSince the early 2000s, the video game industry has seen extraordinary booms in product development and market growth, with the total number of video game players globally reaching 2.69 billion by the end of 2020. Despite the rapid growth of the industry, there is little recent data investigating the time adult video game players spend sedentary playing video games and the time they spent engaged in physical activity. The purpose of this quantitative, cross-sectional, non-experimental survey study is to describe the frequency and duration of video game play and physical activity in adult video game players.MethodsParticipants completed an online survey, evaluating their demographic and health history information, video game play, and physical activity behaviors.ResultsThe study used data from a total of 221 participants (Males = 153, Females = 68). The mean age of the participants was 27.29 (SD 7.27) years. Of the 221 participants, 145 identified as casual players, 50 amateurs, 24 semi-professionals, and 2 professionals. The participants spent over five days per week and an average of 26.56 h per week playing video games. Personal computers were reported to have the longest duration of play of the four platforms investigated (17.59 h per week). The total amount of time participants spent engaged in cumulative moderate-to-vigorous physical activity (MVPA) was an average of 15.43 (SD 16.79) hours per week. The majority of this time was spent engaged in occupational physical activity (5.11 h per week). Participants spent 2.39 h per week engaged in leisure time MVPA.ConclusionOur results indicate an increase in VG play compared to 2018, suggesting United States adult video game players may be more at risk for detrimental effects to their physical health. This could be attributed to the habits formed during the COVID-19 pandemic, the influences from video genre game play mechanics, and the social aspects of playing video games with friends. Future research should focus on developing research methodologies that will objectively measure adult video game player frequencies and durations in video game play alongside extensive observation of different video gameplay mechanic genres and their relationships with physical activity.